LAWS ON THE ASSIGNMENT TO CLERICAL SERVICE IN TURKESTAN (BASED ON MATERIALS FROM THE GOVERNOR-GENERAL'S OFFICE) - Ergashev Bakhtiyar Ergashevich (American Journals Publishing, 2024)
Source study of the history of the Chancellery of the Governor-General in Turkestan requires the analysis of a large number of documents to establish the objective reasons for the activities of the executive body. This article analyzes information about the laws on appointment to church service in Turkestan.
Keywords: Turkestan, governorship, church service, laws, source studies.